High-performance metalized film capacitor
By adding Bi2MoO6@ZIF-8@g-C3N4 composite filler to the epoxy resin encapsulation layer of the film capacitor, the problem of internal fire in high-temperature flame environment is solved, and the ablation and fire resistance of the capacitor is significantly improved and the capacitor is extended. The explosion time was eliminated and prevented the spread of large areas of fire.
Patent Information
- Application Number
- CN202411446379.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Existing film capacitors are prone to internal fires in high-temperature flame environments, resulting in large-area fires, and lack of ablation and fire resistance, making it difficult to effectively prevent fire from burning through in high-temperature environments.
Bi2MoO6@ZIF-8@g-C3N4 composite filler is added to the high-performance epoxy resin adhesive, and the epoxy resin encapsulation layer is made by ultraviolet light curing, replacing the traditional alumina filler, significantly improving the ablation and fire resistance of the capacitor. performance.
In a high-temperature flame environment, extend the explosion time of the capacitor, reduce the risk of internal fire, improve the ablation resistance of the capacitor, and prevent large-area fire from spreading.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of high-performance metallized film capacitors, and in particular to high-performance metallized film capacitors. Background Art
[0002] Film capacitors are also called plastic film capacitors, which use plastic film as dielectric.
[0003] The structure of an existing film capacitor generally includes a capacitor housing, a capacitor core, and an epoxy resin encapsulation layer used to completely encapsulate the capacitor core. The epoxy resin encapsulation layer used is generally made of epoxy resin adhesive doped with fillers (such as spherical alumina) and then cured.
[0004] With the application of film capacitors in the field of new energy vehicles, if a local fire occurs, capacitors are commonly used and large-volume electronic components, and their own burning and fire resistance characteristics are increasingly stringent. Generally, capacitors have a certain energy storage function. Therefore, if a breakdown explosion occurs in a high-temperature environment, it is okay. At least one of the two pins of the capacitor will be cut off instantly, so that the capacitor can be in an open circuit state instantly, and it is not easy to cause a large-scale fire. However, in actual situations, the inside of the capacitor will often be burned through under the continuous burning of high-temperature flames, resulting in serious internal fires, which intensifies the surrounding fire and easily leads to large-scale fires.
[0005] Based on this, the present invention is proposed. Summary of the invention
[0006] The specific technical solutions of the present invention are as follows:
[0007] A high-performance metallized film capacitor comprises a capacitor shell, a capacitor core located inside the capacitor shell, and an epoxy resin encapsulation layer used to completely wrap the capacitor core. The epoxy resin encapsulation layer is made by curing a high-performance epoxy resin adhesive at room temperature under ultraviolet light with a UV wavelength of 360-420nm. The high-performance epoxy resin adhesive is made by mixing epoxy resin adhesive and high-performance composite filler.
[0008] In an optional embodiment, the high-performance composite filler is Bi2MoO6@ZIF-8@g-C3N4.
[0009] In an optional embodiment, the preparation method of Bi2MoO6@ZIF-8@g-C3N4 comprises the following steps:
[0010] Step 1. Preparation of Bi2MoO6@ZIF-8
[0011] The metal organic framework material ZIF-8 and Bi2MoO6 are added to an alcohol solvent, mixed, stirred and dispersed, and then sent into a reflux reactor, first filled with nitrogen to exhaust the air in the reflux reactor, and then refluxed for 12 to 24 hours. After the reaction is completed, the product is centrifuged, washed with ethanol for multiple times, separated, and dried to obtain Bi2MoO6@ZIF-8;
[0012] Step 2: Preparation of Bi2MoO6@ZIF-8@g-C3N4
[0013] After Bi2MoO6@ZIF-8, g-C3N4 and an organic solvent are mixed and stirred evenly, ultrasonic dispersion is first performed for 5 minutes, and then megasonic dispersion is performed at a temperature of 0°C for 10 to 15 minutes, and then the filter is filtered, and the filter residue is dried and ground to obtain the Bi2MoO6@ZIF-8@g-C3N4.
[0014] In an optional embodiment, in step 1, the mass ratio of the metal organic framework material ZIF-8 and Bi2MoO6 is (3 to 3.1):1.
[0015] In an optional embodiment, in step 1, the alcohol solvent is one or more of methanol, ethanol, propanol, and butanol.
[0016] In an optional embodiment, in step 1, the mass volume ratio of the metal organic framework material ZIF-8 to the alcohol solvent is 1:(300-400).
[0017] In an optional embodiment, in step 2, the mass ratio of Bi2MoO6@ZIF-8 to g-C3N4 is 10:(1.1~1.3).
[0018] In an optional embodiment, in step 2, the mass volume ratio of Bi2MoO6@ZIF-8 to the organic solvent is 1:(20-25).
[0019] In an optional embodiment, in step 2, the ultrasonic frequency during ultrasonic dispersion is 20 kHz, and the megasonic frequency during megasonic dispersion is 0.81 MHz.
[0020] In an optional embodiment, in step 1, the drying temperature is 65-80°C;
[0021] In step 2, the drying temperature of the filter residue is 65-80°C.
[0022] In the present invention, the high-performance metallized film capacitor adopts Bi2MoO6@ZIF-8@g-C3N4 to replace the existing fillers such as alumina, and mixes it into the epoxy resin adhesive to prepare a high-performance epoxy resin adhesive. The high-performance epoxy resin adhesive is used to encapsulate the capacitor, which can significantly improve the ablation and fire resistance of the capacitor. DETAILED DESCRIPTION
[0023] The present invention will be further explained below in conjunction with specific embodiments.
[0024] Example 1
[0025] A high-performance metallized film capacitor comprises a capacitor shell, a capacitor core located inside the capacitor shell, and an epoxy resin encapsulation layer used to completely wrap the capacitor core. The epoxy resin encapsulation layer is made by curing a high-performance epoxy resin adhesive at room temperature under ultraviolet light with a UV wavelength of 360-420nm. The high-performance epoxy resin adhesive is made by mixing epoxy resin adhesive and high-performance composite filler.
[0026] The high-performance composite filler is Bi2MoO6@ZIF-8@g-C3N4, and the mass ratio of Bi2MoO6@ZIF-8@g-C3N4 to epoxy resin adhesive is 1:4. The preparation method of Bi2MoO6@ZIF-8@g-C3N4 comprises the following steps:
[0027] Step 1. Preparation of Bi2MoO6@ZIF-8
[0028] The metal organic framework material ZIF-8 and Bi2MoO6 are added to an alcohol solvent, mixed, stirred and dispersed, and then sent into a reflux reactor, first filled with nitrogen to exhaust the air in the reflux reactor, and then refluxed for 12 hours. After the reaction, the product is centrifuged, washed with ethanol for multiple times and separated, and dried at 65°C to obtain Bi2MoO6@ZIF-8; wherein the mass ratio of the metal organic framework material ZIF-8 to Bi2MoO6 is 3:1. The alcohol solvent is ethanol. The mass volume ratio of the metal organic framework material ZIF-8 to the alcohol solvent is 1:300.
[0029] Step 2: Preparation of Bi2MoO6@ZIF-8@g-C3N4
[0030] After Bi2MoO6@ZIF-8, g-C3N4 and organic solvent are mixed and stirred evenly, ultrasonic dispersion is first performed for 5 minutes, and then megasonic dispersion is performed at a temperature of 0°C for 10 minutes, and then the filter is filtered, and the filter residue is dried at 65°C and ground to obtain the Bi2MoO6@ZIF-8@g-C3N4. Among them, the mass ratio of Bi2MoO6@ZIF-8 to g-C3N4 is 10:1.1. The mass volume ratio of Bi2MoO6@ZIF-8 to organic solvent is 1:20. The ultrasonic frequency during ultrasonic dispersion is 20kHz, and the megasonic frequency during megasonic dispersion is 0.81MHz.
[0031] Example 2
[0032] A high-performance metallized film capacitor comprises a capacitor shell, a capacitor core located inside the capacitor shell, and an epoxy resin encapsulation layer used to completely wrap the capacitor core. The epoxy resin encapsulation layer is made by curing a high-performance epoxy resin adhesive at room temperature under ultraviolet light with a UV wavelength of 360-420nm. The high-performance epoxy resin adhesive is made by mixing epoxy resin adhesive and high-performance composite filler.
[0033] The high-performance composite filler is Bi2MoO6@ZIF-8@g-C3N4, and the mass ratio of Bi2MoO6@ZIF-8@g-C3N4 to epoxy resin adhesive is 1:4. The preparation method of Bi2MoO6@ZIF-8@g-C3N4 comprises the following steps:
[0034] Step 1. Preparation of Bi2MoO6@ZIF-8
[0035] The metal organic framework material ZIF-8 and Bi2MoO6 are added to an alcohol solvent, mixed, stirred and dispersed, and then sent into a reflux reactor, first filled with nitrogen to exhaust the air in the reflux reactor, and then refluxed for 12 hours. After the reaction, the product is centrifuged, washed with ethanol for multiple times and separated, and dried at 70°C to obtain Bi2MoO6@ZIF-8; wherein the mass ratio of the metal organic framework material ZIF-8 to Bi2MoO6 is 3:1. The alcohol solvent is methanol. The mass volume ratio of the metal organic framework material ZIF-8 to the alcohol solvent is 1:330.
[0036] Step 2: Preparation of Bi2MoO6@ZIF-8@g-C3N4
[0037] After Bi2MoO6@ZIF-8, g-C3N4 and organic solvent are mixed and stirred evenly, ultrasonic dispersion is first performed for 5 minutes, and then megasonic dispersion is performed at a temperature of 0°C for 12 minutes, and then the filter is filtered, and the filter residue is dried at 70°C and ground to obtain the Bi2MoO6@ZIF-8@g-C3N4. The mass ratio of Bi2MoO6@ZIF-8 to g-C3N4 is 10:1.2. The mass volume ratio of Bi2MoO6@ZIF-8 to organic solvent is 1:22. The ultrasonic frequency during ultrasonic dispersion is 20kHz, and the megasonic frequency during megasonic dispersion is 0.81MHz.
[0038] Example 3
[0039] A high-performance metallized film capacitor comprises a capacitor shell, a capacitor core located inside the capacitor shell, and an epoxy resin encapsulation layer used to completely wrap the capacitor core. The epoxy resin encapsulation layer is made by curing a high-performance epoxy resin adhesive at room temperature under ultraviolet light with a UV wavelength of 360-420nm. The high-performance epoxy resin adhesive is made by mixing epoxy resin adhesive and high-performance composite filler.
[0040] The high-performance composite filler is Bi2MoO6@ZIF-8@g-C3N4, and the mass ratio of Bi2MoO6@ZIF-8@g-C3N4 to the epoxy resin adhesive is 1:4.
[0041] The preparation method of Bi2MoO6@ZIF-8@g-C3N4 comprises the following steps:
[0042] Step 1. Preparation of Bi2MoO6@ZIF-8
[0043] The metal organic framework material ZIF-8 and Bi2MoO6 are added to an alcohol solvent, mixed, stirred and dispersed, and then sent to a reflux reactor, first filled with nitrogen to exhaust the air in the reflux reactor, and then refluxed for 24 hours. After the reaction, the product is centrifuged, washed with ethanol for multiple times and separated, and dried at 80°C to obtain Bi2MoO6@ZIF-8; wherein the mass ratio of the metal organic framework material ZIF-8 to Bi2MoO6 is 3.1:1. The alcohol solvent is propanol. The mass volume ratio of the metal organic framework material ZIF-8 to the alcohol solvent is 1:400.
[0044] Step 2: Preparation of Bi2MoO6@ZIF-8@g-C3N4
[0045] After Bi2MoO6@ZIF-8, g-C3N4 and organic solvent are mixed and stirred evenly, ultrasonic dispersion is first performed for 5 minutes, and then megasonic dispersion is performed at a temperature of 0°C for 15 minutes, and then the filter is filtered, and the filter residue is dried at 80°C and ground to obtain the Bi2MoO6@ZIF-8@g-C3N4. The mass ratio of Bi2MoO6@ZIF-8 to g-C3N4 is 10:1.3. The mass volume ratio of Bi2MoO6@ZIF-8 to organic solvent is 1:25. The ultrasonic frequency during ultrasonic dispersion is 20kHz, and the megasonic frequency during megasonic dispersion is 0.81MHz.
[0046] Comparative Example 1
[0047] The only difference between this example and Example 1 is that Bi2MoO6 is used to replace Bi2MoO6@ZIF-8@g-C3N4 in this example, and the rest is the same as Example 1.
[0048] Comparative Example 2
[0049] The only difference between this example and Example 1 is that ZIF-8 is used to replace Bi2MoO6@ZIF-8@g-C3N4 in this example, and the rest is the same as Example 1.
[0050] Comparative Example 3
[0051] The only difference between this example and Example 1 is that g-C3N4 is used to replace Bi2MoO6@ZIF-8@g-C3N4 in this example, and the rest is the same as Example 1.
[0052] Comparative Example 4
[0053] The only difference between this example and Example 1 is that Bi2MoO6@ZIF-8 is used to replace Bi2MoO6@ZIF-8@g-C3N4 in this example, and the rest is the same as Example 1.
[0054] Comparative Example 5
[0055] The only difference between this example and Example 1 is that in this example, a mixture of Bi2MoO6, ZIF-8 and g-C3N4 is used to replace Bi2MoO6@ZIF-8@g-C3N4, and the rest is the same as Example 1.
[0056] Comparative Example 6
[0057] The only difference between this example and Example 1 is that in this example, a mixture of Bi2MoO6@ZIF-8 and g-C3N4 is used to replace Bi2MoO6@ZIF-8@g-C3N4, and the rest is the same as Example 1.
[0058] Comparative Example 7
[0059] The difference between this example and Example 1 is that in step 2 of this example, ultrasonic dispersion is first performed for 5 minutes, and then megasonic dispersion is performed at a temperature of 20° C. for 10 minutes. The rest is the same as Example 1.
[0060] Comparative Example 8
[0061] The difference between this example and Example 1 is that in step 2 of this example, ultrasonic dispersion is performed at a temperature of 0° C. for 20 min, and the rest is the same as Example 1.
[0062] 《Characterization of Ablation and Fire Test》
[0063] Use a flame gun with a flame temperature of 1000℃ to burn the capacitor shell, and use a bare wire to connect a voltage of 1008V (breakdown voltage) to the capacitor (rated voltage is 630V). At the same time, use a stopwatch to time until an explosion or fire occurs, and record the time taken for the explosion or fire to occur. The test results are shown in Table 1:
[0064] Table 1
[0065] Test results Example 1 It exploded after burning for 5 seconds, and caught fire inside the shell after burning for another 21 seconds. Example 2 It exploded after burning for 5 seconds, and caught fire inside the shell after burning for another 22 seconds. Example 3 It exploded after burning for 5 seconds, and caught fire inside the shell after burning for another 20 seconds. Reference capacitor After burning for 3 seconds, the shell caught fire, but there was no explosion. Comparative Example 1 After burning for 4 seconds, the shell caught fire, but there was no explosion. Comparative Example 2 After burning for 3 seconds, the shell caught fire, but there was no explosion. Comparative Example 3 After burning for 2 seconds, the shell caught fire, but there was no explosion. Comparative Example 4 After burning for 5 seconds, the shell caught fire and there was no explosion. Comparative Example 5 After burning for 5 seconds, the shell will catch fire and produce an explosion 3 seconds after the fire starts. Comparative Example 6 After burning for 6 seconds, the shell will catch fire, and an explosion will occur 4 seconds after the fire starts.
[0066] In Table 1, the reference capacitor is an existing thin film capacitor, and the epoxy resin encapsulation layer used therein is made by doping the existing epoxy resin adhesive with spherical alumina and then curing it. The mass ratio of spherical alumina to the existing epoxy resin adhesive (purchased from Beijing Luhang Hangte Technology Co., Ltd.) is 1:4; UV wavelength 360-420nm ultraviolet light is used to assist curing during the curing process.
[0067] Because in a high temperature environment, the local film is easily softened, causing the voltage in the local area to instantly reach the breakdown voltage. Only under the test of the dual harsh environment of breakdown voltage and high temperature burning can the capacitor's resistance to ablation and fire be reflected.
[0068] In Table 1, if the film capacitor explodes first and then catches fire after burning for a period of time, this is an ideal state. Because during use, the film capacitor will generate a huge impact force at the moment of explosion, so that at least one of the two leads of the capacitor will be cut off instantly, so that the capacitor can be in a circuit-breaking state instantly and the power supply is cut off. Even if it is burned continuously for a long time in the later stage, it will only be charred; only after continuous burning for a period of time will the epoxy resin encapsulation layer inside it burn on a large scale.
[0069] However, if the film capacitor burns first and then explodes, it is meaningless because the capacitor has already caught fire and it does not matter whether it explodes or not.
[0070] Stirring Test
[0071] If g-C3N4 is not completely composited with Bi2MoO6@ZIF-8, when the powder prepared in step 2 (hereinafter referred to as product powder) is poured into the epoxy resin adhesive and stirred, it is found that due to the light weight of g-C3N4, some of the product powder always floats on the surface of the epoxy resin adhesive, and the difference ΔX between the solid content of the upper and lower adhesive layers is large.
[0072] The test results of Example 1, Comparative Example 7 and Comparative Example 8 are shown in Table 2:
[0073] Table 2
[0074] Test results Example 1 After stirring for 30 minutes, ΔX = 0.2% Comparative Example 7 After stirring for 60 min, ΔX = 5.9% Comparative Example 8 After stirring for 60 min, ΔX = 13.6%
[0075] It can be seen that in the composite process of g-C3N4 and Bi2MoO6@ZIF-8, the use of low temperature combined with megasonic dispersion can significantly improve the composite effect and is beneficial to the combination of g-C3N4 and Bi2MoO6@ZIF-8.
[0076] In the above embodiment, the CAS number of the metal organic framework material ZIF-8 is 59061-53-9. The mass volume ratio is the ratio between the mass of the first substance and the volume of the second substance. For example, the mass volume ratio of the metal organic framework material ZIF-8 to the alcohol solvent is 1:300, corresponding to the mass of the metal organic framework material ZIF-8 being 1g and the volume of the alcohol solvent being 300ml. g-C3N4 is graphite phase carbon nitride, purchased from Suzhou Kaifa New Material Technology Co., Ltd. The capacitor shells are all aluminum shells.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-performance metallized film capacitor, comprising a capacitor housing, a capacitor core located inside the capacitor housing, and an epoxy resin encapsulation layer for completely encapsulating the capacitor core, characterized in that: The epoxy resin encapsulation layer is made by curing a high-performance epoxy resin adhesive at room temperature under ultraviolet light with a UV wavelength of 360-420nm. The high-performance epoxy resin adhesive is made by mixing epoxy resin adhesive and high-performance composite filler.
2. A high performance metallized film capacitor according to claim 1, characterized in that: The high-performance composite filler is Bi2MoO6@ZIF-8@g-C3N4.
3. A high performance metallized film capacitor according to claim 2, characterized in that: The preparation method of Bi2MoO6@ZIF-8@g-C3N4 comprises the following steps: Step 1. Preparation of Bi2MoO6@ZIF-8 The metal organic framework material ZIF-8 and Bi2MoO6 are added to an alcohol solvent, mixed, stirred and dispersed, and then sent into a reflux reactor, first filled with nitrogen to exhaust the air in the reflux reactor, and then refluxed for 12 to 24 hours. After the reaction is completed, the product is centrifuged, washed with ethanol for multiple times, separated, and dried to obtain Bi2MoO6@ZIF-8; Step 2: Preparation of Bi2MoO6@ZIF-8@g-C3N4 After Bi2MoO6@ZIF-8, g-C3N4 and an organic solvent are mixed and stirred evenly, ultrasonic dispersion is first performed for 5 minutes, and then megasonic dispersion is performed at a temperature of 0°C for 10 to 15 minutes, and then the filter is filtered, and the filter residue is dried and ground to obtain the Bi2MoO6@ZIF-8@g-C3N4.
4. A high performance metallized film capacitor according to claim 3, characterized in that: In step 1, the mass ratio of the metal organic framework material ZIF-8 and Bi2MoO6 is (3 to 3.1):
1.
5. A high performance metallized film capacitor according to claim 3, characterized in that: In step 1, the alcohol solvent is one or more of methanol, ethanol, propanol and butanol.
6. A high performance metallized film capacitor according to claim 3, characterized in that: In step 1, the mass volume ratio of the metal organic framework material ZIF-8 to the alcohol solvent is 1:(300-400).
7. A high performance metallized film capacitor according to claim 1, characterized in that: In step 2, the mass ratio of Bi2MoO6@ZIF-8 to g-C3N4 is 10:(1.1~1.3).
8. A high performance metallized film capacitor according to claim 1, characterized in that: In step 2, the mass volume ratio of Bi2MoO6@ZIF-8 to the organic solvent is 1:(20-25).
9. A high performance metallized film capacitor according to claim 1, characterized in that: In step 2, the ultrasonic frequency during ultrasonic dispersion is 20 kHz, and the megasonic frequency during megasonic dispersion is 0.81 MHz.
10. The high performance metallized film capacitor according to claim 1, characterized in that: In step 1, the drying temperature is 65-80°C; In step 2, the drying temperature of the filter residue is 65-80°C.
Citation Information
Patent Citations
Preparation method and application of bismuth molybdate-metal organic framework composite catalyst
CN114210371A
Preparation method of composite material Bi2MoO6 / ZIF-67
CN115178297A
Ultrathin high-temperature-resistant polypropylene capacitor film and manufacturing method thereof
CN115322478A
MOF modified epoxy resin, adhesive and preparation method of MOF modified epoxy resin
CN116375977A
Method for manufacturing film capacitor and film capacitor
JP2012234932A